Making asynchronous online learning more learner-oriented: An integrated conceptual model with applications for course design and instruction. Issue 2 (1st February 2016) - Majeski, Robin A.; Stover, Merrily; Ronch, Judah
Abstract: Aging professionals have not always effectively communicated about aging to the general public (Feather, 2015). Due at least in part to this, the public often holds inaccurate, ageist beliefs about older adults and aging services/gerontology has been difficult to promote as a desirable career option (Feather, 2015). The authors address this important issue by proposing a comprehensive learner-oriented, thinking slow (Kahneman, 2013) approach for the asynchronous online gerontology/aging services classroom in order to move students beyond ageist stereotypes to adopt richer views of aging. For asynchronous online aging services/gerontology courses to be learner-oriented and encourage thinking slow, they need to be based on an understanding of cognition and motivation for learning. Thus, this paper presents a theoretical model which addresses the cognitive and motivational aspects of learning in asynchronous online aging services/gerontology courses. It does this by integrating the Cognitive Affective Theory of Learning with Media (CATLM) (Moreno, 2006; Mayer, 2009; Moreno & Mayer, 2007), Pekrun and Stephens' (2010) Control Value Theory of Achievement Emotion, and further develops the components of the model related to long-term memory storage and retrieval by using insights from Brown, Roediger, and McDaniel (2014). Also, the paper presents practical instructional, course design, and communication strategies as these relate to the components of human cognition and motivation in the model to ensure learner success, satisfaction, and the adoption of more open-mindedness with ways of thinking about aging.